(untitled) (Research, Society and Development, 2022)
Non-ionic surfactants are important chemical products, they are raw materials in the production of solvents, detergents, paints etc. They are produced through the ethoxylation reaction, that takes place in semi-batch reactors, by reacting between ethylene oxide with an organic substrate in the presence of a basic catalyst such as KOH. Due to the instability and reactivity of ethylene oxide, ethoxylation is a highly exothermic reaction, which requires the presence of a heat exchange system, with strict control of temperature and pressure that prevents explosions. In this paper, the ethoxylation of nonylphenol to obtain nonylphenol 9 EO (nonoxynol 9) was simulated in Aspen Plus Dynamics® where temperature, pressure, and batch flow controls were implemented and evaluated. The results obtained showed that the control from the response of ∆P (difference between the operating limit pressure and the real reactor pressure) is effective, consequently, the reactor pressure remains controlled and lower than the limiting pressures of the system throughout the reaction process.